Assessing the promotion of urine-diverting dry toilets through school-based demonstration facilities in Kalisizo, Uganda - Trimmer, John T.; Nakyanjo, Neema; Ssekubugu, Robert; Sklar, Marc; Mihelcic, James R.; Ergas, Sarina J. (Journal of Water, Sanitation and Hygiene for Development, 2016)
Urine-diverting dry toilets (UDDTs) are designed to recover nutrients and organic matter from human excreta for agricultural reuse. Their wider implementation could help address problems in areas where water scarcity limits coverage of sanitation systems and declining soil fertility jeopardizes nutritional security. Demonstration facilities can improve stakeholders’ views of UDDTs; however, it is uncertain whether these facilities should be located at households or institutions. Using a novel methodological approach that included qualitative data collection before and after introduction of demonstration UDDTs and quantitative monitoring of treatment conditions, this study evaluated changes in local attitudes and knowledge resulting from a UDDT promotion strategy at two primary schools in Uganda. Before introduction, students had little knowledge of UDDT facilities, while most attitude-related statements conveyed negative viewpoints and skepticism. After introduction and six months of operation, students exhibited increased knowledge, and 68% of attitude-related statements conveyed positive opinions that focused on the UDDTs’ long-term economic value and their role in creating a more hygienic school environment. These changes were seen in facility users and in other students at the schools who were non-users. In the future, with these improved perceptions, students could become compelling representatives for UDDTs within their communities, potentially increasing adoption.
Keywords: Ecological sanitation; Food security; Health; Latrine; Sub-Saharan Africa; sustainable development goals